A possible role of Bacteroides fragilis enterotoxin in the aetiology of colorectal cancer - KARAHASAN, AYŞEGÜL; GÜLLÜOĞLU, MAHMUT BAHADIR; ÜLGER, NURVER (ELSEVIER SCI LTD, 2006)
The prevalence of enterotoxigenic Bacteroides fragilis (ETBF) was investigated in stool specimens from 73 patients with colorectal cancer and from 59 control patients. Stool specimens were cultured on Bacteroides Bile Esculin agar and B. fragilis was identified by conventional methods. After DNA extraction, the enterotoxin gene (bft) was detected by PCR in 38% of the isolates from colorectal cancer patients, compared with 12% of the isolates from the control group (p 0.009). This is the first study demonstrating an increased prevalence of ETBF in colorectal cancer patients.
Keywords: Bacteroides fragilis; bft gene; colorectal cancer; enterotoxin; fragilysin; PCR; INTESTINAL EPITHELIAL-CELLS; INFLAMMATORY-BOWEL-DISEASE; EXPRESSION; CHILDREN; METALLOPROTEASE; SECRETION; DIARRHEA; PROTEIN; TOXIN; IL-8